Survey on anomaly propagation research for social networks - LU Kun; ZHANG Jiayu; ZHANG Hongli; FANG Binxing (Tongxin xuebao)
Anomaly propagation is a non-traditional mode of information dissemination that frequently occurs in today’s online social networks. To fully comprehend the overall process of anomaly propagation in social networks, the anomaly propagation lifecycle system was classified into incubation period, diffusion period, climax period, and decline period. In response to the scientific problems existing in different stages of anomaly propagation, four popular research fields of anomaly information, anomaly users, anomaly propagation, and propagation containment were defined and divided respectively from micro and macro perspectives. The main research tasks and related research progress in the four current research areas were reviewed and summarized in detail, problems in existing methods were analyzed. The future research directions on anomaly propagation in social networks were prospected, providing convenience for subsequent research.